Applying geospatial technology to landslide susceptibility assessment. - Safaei, Mehrdad; Omar, Husaini; Ghiasi, Vahed; Yousof, Zenoddin B.M. (Oklahoma State University, 2010)

(untitled)
Landslide or mass movement is a phenomenon of denudation process, whereby soil or rock is displaced along the slope by mainly gravitational forces, usually occurring on unstable slopes due to various reasons. The reasons can be either natural or man-made. Geospatial technology includes Geographic Information Systems (GIS) and Remote sensing (RS) tools and methods for improved landslide inventory mapping and landslide assessment and susceptibility. The application of geospatial sciences has spread very fast and wide over the past few decades in the world. This paper presents a summary and a classification of the recent developments in different approaches to landslide hazards while using GIS modeling for the analysis of the causative factors. The application of GIS is an essential tool in the data analysis and slope stability modeling that has been recognized worldwide. In addition, this paper indicates the application of various remote sensing techniques in order to prepare a landslide data collection. It also discusses the use of advanced spatial technology such as space borne SAR and also the present technologyof satellite based remote sensing that can be used for qualitative prediction of landslide with high-resolution sensors that aids in the preparation of better quality landslide hazard mapping.